2021
DOI: 10.26603/001c.18825
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing and Integration of Cervical Manual Therapy and Vestibulo-oculomotor Therapy for Concussion Symptoms: Retrospective Analysis

Abstract: Background BackgroundAfter concussion many people have cervicogenic headache, visual dysfunction, and vestibular deficits that can be attributed to brain injury, cervical injury, or both. While clinical practice guidelines outline treatments to address the symptoms that arise from the multiple involved systems, no preferred treatment sequence for post-concussion syndrome has emerged. Purpose PurposeThis study sought to describe the clinical and patient-reported outcomes for people with post-concussion symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This positive effect can be sustained at 3 and 6 months 49 , although this latter trial lacked a control group, which detracts from its methodological quality. Wong et al 50 combined manual therapy, visual exercises, and vestibular rehabilitation in…”
Section: Discussionmentioning
confidence: 99%
“…This positive effect can be sustained at 3 and 6 months 49 , although this latter trial lacked a control group, which detracts from its methodological quality. Wong et al 50 combined manual therapy, visual exercises, and vestibular rehabilitation in…”
Section: Discussionmentioning
confidence: 99%
“…During initial evaluation, patients completed the PCSS, BIVSS, and DHI. Patients were screened for cervicogenic complaints and referred to a PT team member specializing in cervical spine for further evaluation and treatment for the cervical-musculoskeletal domain [13,16]. Evaluations of the motor function and vestibulo-oculomotor domains were completed and structured therapies were based on identified impairment(s).…”
Section: Designmentioning
confidence: 99%
“…Cervical musculoskeletal and vestibulo-ocular PT care models have been proposed to address this gap. Multiple studies have concluded that addressing cervical spine limitations and Benign Paroxysmal Positional Vertigo (BPPV) symptoms, integrated with visual and vestibular rehabilitation, can improve clinical and patient-reported outcomes across all systems [13,14]. In addition, Ziaks et al 2021 proposed that phased primitive reflex integration therapy targeting complex movements and Brain-Body Integration (BBI) as a precursor to vision and vestibular therapy can have improved motor function postconcussion [15].…”
Section: Introductionmentioning
confidence: 99%
“…Concussions can lead to various symptoms that are usually short lasting and are not necessarily specific to concussions (Iverson et al, 2020). For instance, concussion-related symptoms can also be present with cervical or vestibular dysfunctions (Cheever et al, 2016;Leddy et al, 2015;Leslie & Craton, 2013;Wong et al, 2021). The four main domains of clinical symptoms described in the literature are cognitive (e.g.…”
Section: Clinical Symptomsmentioning
confidence: 99%